Genomic identification and degradation testing of hydrocarbon-utilizing bacteria isolated from soil in Eleme Local Government Area of Rivers State, Nigeria - Chunwafor, Mavis Iziegbe; Ogbonda, Kemka Humphrey; Okwelle, Austin Achinike (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
As a result of industrialization, environmental pollution by hydrocarbon is almost inevitable since they are the highest cause of contamination of soil. Since hydrocarbon pollution is an issue of serious consequence and concern, it is important to devise a means to degrade them without causing more harm to the soil and its inhabitants than it is with chemical methods. This research is therefore focused on the identification and degradability test of hydrocarbon-utilizing bacteria isolated from contaminated soil in the Eleme local government area of Rivers state, Nigeria. Soil samples from different contaminated sites were collected aseptically and isolation of the bacteria was carried out using the spread plate vapour transfer method for hydrocarbon-utilizing bacteria. Zymo Quick DNA Fungal/Bacterial Kit was used for the DNA extraction. A fragment of their 16S ribosomal ribonucleic acid (16S rRNA) gene was extracted for all isolates and amplified with polymerase chain reaction (PCR) with the universal primer set 27F: AGAGTTTGATCMTGGCTCAG and 1525R: AAGGAGGTGWTCCARCCGCA. Bacteria that were identified include: Sinomonas halotolerant strain, Priestia flexa strain, Rhizobium freireiI strain, Burkholderia stagnalis strain, Serratia marcescens strain, Burkholderia arboris strain, Ectobacillus funiculus strain and Priestia megaterium strain with similarity 98-100% to the closest GenBank match. The bacteria were further examined for hydrocarbon compound degradation ability using turbidity test and they showed different capabilities. Of all the bacteria isolates, Priestia flexa strain, Serratia marcescens strain, Burkholderia stagnalis strain and Rhizobium freireiI strain showed very high level of degradation ability of all the hydrocarbons (Used oil, Kerosene DPK, Diesel AGO and Fuel PMS) compounds. PMS was the most difficult to degrade by these bacteria. The bacteria isolated from this research can be used for bioremediation of hydrocarbon-contaminated sites instead of other methods.